2003
DOI: 10.1556/aagr.51.2003.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic attributes and seed yield of sunflower (Helianthus annuus L.) as influenced by different levels and ratios of nitrogen and phosphorus fertilizers

Abstract: A field experiment was conducted at the Main Research Station, University of Agricultural Sciences, Dharwad, India, on medium black soils during the kharif (wet) season of 1999. The experiment was laid out in a randomized complete block design with varying N/P ratios (0.67 to 2.00) along with a control with a constant level of potassium (60 kg ha -1). The results revealed that the number of green leaves plant -1 , the dry matter accumulation in the leaves, leaf area (dm 2 plant -1 ) and leaf area index (LAI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
1
Order By: Relevance
“…Contrary to this experiment, Rawson and Turner (1983), Hall et al (1985) and Thavaprakash et al (2003) concluded that there was a close positive correlation between the LAI values and the yield of sunflower. The experimental data of this study proved a close negative correlation between LAI max and sowing date in 2013 and 2014 (r = -0.920**, r = 0.813**).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Contrary to this experiment, Rawson and Turner (1983), Hall et al (1985) and Thavaprakash et al (2003) concluded that there was a close positive correlation between the LAI values and the yield of sunflower. The experimental data of this study proved a close negative correlation between LAI max and sowing date in 2013 and 2014 (r = -0.920**, r = 0.813**).…”
Section: Resultscontrasting
confidence: 61%
“…There was little assimilatory leaf area even from the end of August to the beginning of September in late sowing of sunflower (Figure 1). Sunflower cultivars gave their LAI max values in the flowering phenophases, which can be characterised by around 5.0 m 2 /m 2 as in the studies of Thavaprakash et al (2003) and Debaeke et al (2014). Cui et al (2000) proved that the rational increase of leaf area is a key crop physiological factor to increase the yields of sunflower.…”
Section: Resultsmentioning
confidence: 71%
“…Sunflower (Helianthus annuus L.) is an important oilseed crop which ranks the third after soybean and peanut along with other oil seed crops like (canola and cotton) which contributes considerably to consumable oil in the world [31]. Sunflower occupies an important place in oil seed crops because of short duration as well as its ability to adapt wide range of climate and soil conditions [32]. This crop has an ideal place in the present cropping system but due to some constraints the average yield is much lower than world's average.…”
Section: Introductionmentioning
confidence: 99%